2002
DOI: 10.1124/jpet.102.037812
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing Strength of a Novel Dopamine Transporter Ligand: Pharmacodynamic and Pharmacokinetic Mechanisms

Abstract: Drugs that block dopamine uptake often function as positive reinforcers but can differ along the dimension of strength or effectiveness as a positive reinforcer. The present study was designed to examine pharmacological mechanisms that might contribute to differences in reinforcing strength between the piperidine-based cocaine analog (ϩ)-methyl 4␤-(4-chlorophenyl)-1-methylpiperidine-3-␣-carboxylate [(ϩ)-CPCA] and cocaine. Drugs were made available to rhesus monkeys (n ϭ 5) for i.v. self-administration under a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
5
25
0
Order By: Relevance
“…drug availability (Balster and Schuster, 1973;Griffiths et al, 1978;Risner and Jones 1976;Bergman et al, 1989). In this regard, double alternation schedules like the one used in the present study previously have been used only in single-lever self-administration studies (Woolverton et al, 2001(Woolverton et al, , 2002. It is noteworthy that functions describing the relation between response allocation and unit dose of drug obtained on the first and second days of the double alternation schedule were comparable and, also, were similar to previously reported effects of these drugs under different choice procedures (Iglauer and Woods, 1974;Paronis et al, 2002;Negus, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…drug availability (Balster and Schuster, 1973;Griffiths et al, 1978;Risner and Jones 1976;Bergman et al, 1989). In this regard, double alternation schedules like the one used in the present study previously have been used only in single-lever self-administration studies (Woolverton et al, 2001(Woolverton et al, , 2002. It is noteworthy that functions describing the relation between response allocation and unit dose of drug obtained on the first and second days of the double alternation schedule were comparable and, also, were similar to previously reported effects of these drugs under different choice procedures (Iglauer and Woods, 1974;Paronis et al, 2002;Negus, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, the cocaine analog HD-23, which takes 60 min to attain significant binding was not as reinforcing in rhesus monkeys as were cocaine or methylphenidate (Lile et al, 2003). The piperazine analog (+)-CPCA binds to DAT more slowly than cocaine and was found to be a less robust reinforcer than cocaine in nonhuman primates (Woolverton et al, 2002). Woolverton et al (2002) have suggested that reinforcing strength may be related to the rate of DAT occupancy over a time frame within 3 min after injection.…”
Section: Discussionmentioning
confidence: 99%
“…The piperazine analog (+)-CPCA binds to DAT more slowly than cocaine and was found to be a less robust reinforcer than cocaine in nonhuman primates (Woolverton et al, 2002). Woolverton et al (2002) have suggested that reinforcing strength may be related to the rate of DAT occupancy over a time frame within 3 min after injection. The rate of drug onset also plays a role in determining its behavioral-stimulant effects, as evidenced by the strong correlation between the time to peak dopamine levels and peak behavioral-stimulant effects in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The method for in vivo binding studies has been described previously (Stathis et al, 1995;Woolverton et al, 2002).…”
Section: In Vivo Bindingmentioning
confidence: 99%
“…In dose-response functions, the ratio data were transformed to the percentage of saline data and analyzed using nonlinear regression analysis assuming a one-site interaction (Prism 3.0, GraphPad, San Diego, CA The time point for 25% of the DAT binding was used because cocaine showed 25% of the displacement of the radioligand binding 2 min after the i.v. injection, a time that appears particularly relevant to the reinforcing effect (Volkow et al, 2000;Woolverton et al, 2002). The time point of 50% of the DAT binding was chosen because it was the maximum binding achieved by an ED 50 dose.…”
Section: In Vivo Bindingmentioning
confidence: 99%